Calculus with Applications (10th Edition)

Published by Pearson
ISBN 10: 0321749006
ISBN 13: 978-0-32174-900-0

Chapter R - Algebra Reference - R.1 Polynomials - R.1 Exercises: 22

Answer

$(x-1)(x+2)(x-3)=x^{3}-2x^{2}-5x+6$

Work Step by Step

$(x-1)(x+2)(x-3)$ First, evaluate $(x-1)(x+2)$ and simplify: $(x-1)(x+2)(x-3)=(x^{2}+2x-x-2)(x-3)=...$ $...=(x^{2}+x-2)(x-3)=...$ Now, evaluate $(x^{2}+x-2)(x-3)$ and simplify again: $...=x^{3}-3x^{2}+x^{2}-3x-2x+6=...$ $...=x^{3}-2x^{2}-5x+6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.